Gender as Pathology: Disease, Degeneration, and Medical Discourse in Late Nineteenth-century Colombia - Hanni Jalil Paier (Revista CS)
This article examines how Colombian doctors and public health officials during the lastdecades of the nineteenth century produced a body of knowledge about the health of thenation’s citizens, using the language and authority of science to speak about a society inneed of redemption and medical intervention. In these cases, gender became an essentialcomponent of elite and medical discourses. Medical doctors and hygienists described femaleidentities either as potentially threatening and therefore degenerative to the nation’s moraland economic fabric or as a “civilizing force” through the mobilization of motherhood andthe reification of the Colombian family as a regenerative site. The doctors and governmentofficials here examined expected women to preserve the family as a unit and inculcate thevalues of order, hygiene and efficiency in the private sphere. If elite constructions of “ideal”female identities mobilized women in their primary function as mothers, preoccupations withthe control of “public women” that upset public order or threatened the family unit rhetoricallyemphasized their deviance. In direct contrast to the feminine ideal, the constructionof the feminine other emphasized moral transgression and sexual promiscuity.